2014
DOI: 10.1080/0305215x.2014.971777
|View full text |Cite
|
Sign up to set email alerts
|

A global optimization algorithm for simulation-based problems via the extended DIRECT scheme

Abstract: This article presents a global optimization algorithm via the extension of the DIviding RECTangles (DIRECT) scheme to handle problems with computationally expensive simulations efficiently. The new optimization strategy improves the regular partition scheme of DIRECT to a flexible irregular partition scheme in order to utilize information from irregular points. The metamodelling technique is introduced to work with the flexible partition scheme to speed up the convergence, which is meaningful for simulation-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…The sensitivity analysis of eDIRECT to different metamodel types by Liu et al (2015b) has also confirmed this finding.…”
Section: Pure Greedy Search On Adaptive Metamodelssupporting
confidence: 70%
See 4 more Smart Citations
“…The sensitivity analysis of eDIRECT to different metamodel types by Liu et al (2015b) has also confirmed this finding.…”
Section: Pure Greedy Search On Adaptive Metamodelssupporting
confidence: 70%
“…As the basis of the unconstrained eDIRECT global optimization algorithm which was proposed by the authors earlier (Liu et al 2015b), the original DIRECT algorithm (Jones et al 1993) has been studied and developed intensively for boxconstrained problems (Sergeyev and Kvasov 2006;Paulavičius and Žilinskas 2013;Liu and Cheng 2014;Paulavičius et al 2014). However, to the best of our knowledge, there is little work of the DIRECT-type algorithm for constrained problems (Jones 2001;Finkel 2005;Paulavičius and Žilinskas 2016).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations